2016
DOI: 10.1093/ofid/ofw234
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis Protection Against Staphylococcus aureus Colonization in People Living With Human Immunodeficiency Virus in an Inner-City Outpatient Population: A Cross-Sectional Study

Abstract: Background.People living with human immunodeficiency virus (PLWH) have been disproportionally affected by methicillin-resistant Staphylococcus aureus (MRSA) colonization and infection, in particular by clones USA300 and USA500. However, the contribution of epidemiological, bacterial, and immunological risk factors to the excess of S aureus in PLWH remain incompletely understood.Methods.In this cross-sectional study, we determined the prevalence and molecular epidemiology of S aureus colonization in 93 PLWH att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
6
0
2
Order By: Relevance
“…The characteristics of each individual, and likewise of health processes, may influence the microbial profile of the hospital and the individual’s mucus. The prevalence of S. aureus in our study seems to be similar to worldwide frequencies reported in other studies of the general population, which have varied from 30 to 74% in various regions of the world, particularly in Latin America [ 12 , 13 ].…”
Section: Main Textsupporting
confidence: 90%
“…The characteristics of each individual, and likewise of health processes, may influence the microbial profile of the hospital and the individual’s mucus. The prevalence of S. aureus in our study seems to be similar to worldwide frequencies reported in other studies of the general population, which have varied from 30 to 74% in various regions of the world, particularly in Latin America [ 12 , 13 ].…”
Section: Main Textsupporting
confidence: 90%
“…This is done by secreting various substances (including serine protease) that cause the release of host antimicrobial peptides. [ 38 , 39 ] A recent study showed that there was a lower probability of S. aureus colonization in the presence of co-colonization by Staphylococcus lugdunensis due to the production of a “lugdunin” molecule by this bacterium, which acts as an antimicrobial agent, reducing the probability of S. aureus colonization. The study showed that, among 187 hospital patients, those who naturally harbored S. lugdunensis in the nose were six times less likely to have S. aureus colonization than those who did not carry it [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. epidermidis has also been shown to influence host colonization by other species, as shown for Staphylococcus aureus (Iwase et al, 2010 ; Park et al, 2011 ). Negative correlations between these two species have been reported in humans, insinuating an antagonism between at least some strains (Frank et al, 2010 ; Sullivan et al, 2016 ). This effect is at least partially due to the secretion of factors that impact on the viability or colonization capacity of other microorganisms (Christensen et al, 2016 ; Janek et al, 2016 ).…”
Section: S Epidermidis As a Member Of Commensal Human Micromentioning
confidence: 99%